BURIALS OF THE EARLY BRONZE AGE IN MOUNTAIN REGIONS OF THE SOUTH-EAST OF AZERBAIJAN - Agalarzade, Anar Mirsamid (History, Archeology and Ethnography of the Caucasus, 2021)
The paper deals with the results of excavations carried out in recent years in the Early Bronze Age kurgans in the mountainous part of the south-eastern region of Azerbaijan. It has been determined that there are several types of burial customs of this period in these small kurgans located on the Komani plateau between Kurekchi and Arvana villages of Yardimly district, on the Azerbaijan - Iran border. Although the Early Bronze Age Telmankend kurgans were excavated in the foothills of the region in the 1960s, such monuments were not excavated or even registered in the highlands. at these grave monuments, which were first discovered by us in the summer pastures in 2014, archaeological excavations began in 2018, and four kurgans were excavated here. Komani kurgans, built at an altitude of 2000 m above sea level, are important in terms of studying the burial customs of the Early Bronze Age semi-nomadic cattle-breeding population. Excavations of Komani kurgans have revealed that the high mountainous area of the south-eastern region of Azerbaijan had been used by the cattle-breeding population since the Early Bronze Age, where they were engaged in seasonal farming and carried out their burials. The lack of grave goods during the burial is explained by their temporary residence in the summer pastures. Undoubtedly, the presence of short-term settlements of cattle-breeding tribes near the kurgans is no exception. Building of Early Bronze Age Komani kurgans in the afore-said area from the chronological viewpoint is distinguished due to their small size. As for the later stages of the Bronze Age, dozens of big kurgans can be found here. However, no archeological excavations have been carried out in any of them so far. Similar burial customs and materials of Komani kurgans are mostly found in the Early Bronze Age monuments of Nakhchivan. Similar burials can be found in other coeval grave monuments of Azerbaijan and in the north-eastern provinces of Iran.